Effekt av sederingsrutin och vikt på höftledsröntgen hos hund - Eriksson, Josefine (2011)
The aim of the study was to investigate whether the sedation method had an effect on the screening result for hip dysplasia (HD). Another aspect considered was if the dog’s weight had an impact on the results. This study was a follow up on the results from an earlier study of sedation routines in Swedish dogs. The breeds included in this study were the same as in the earlier one; German shepherd, Bernese mountain dog, Boxer, Newfoundland, Rottweiler, Saint Bernard, Golden and Labrador Retriever. The analyses were based on data provided by the Swedish Kennel Club (SKC), and included information on all dogs in the SKC database of the concerned breeds screened for HD during 2004-2010. The information included age, weight, registration number of the dog and its parents, hip status, clinic, gender, breed and sedation method. HD is a polygenic trait which means that the phenotype is affected by both genes and environmental factors. A dysplastic hip has a poorly fitted hip socket, which often leads to arthritis and suffering in affected dogs. Environmental factors that can have an impact on whether a dog develops dysplasia or not are for example feeding, weight, age at screening and sedation method. The disease is more common in heavy, large breeds than in small ones. The reason for that can be how fast growing the breed is, and also which size and weight it has. How successful the breed club has been in trying to select healthy dogs to decrease the frequency of HD is another reason for certain breeds to be more commonly dysplastic than others. The heaviest and largest breeds in this study, Newfoundland and Saint Bernard, were found to be the ones with highest frequency of hip dysplasia. Labrador Retriever, Rottweiler and Bernese mountain dog were the healthiest ones, regarding hip status, of the breeds included in the study. In 2000, the SKC decided to join the FCI protocol for examination and grading of HD. The FCI grading scale has five classes, A to E, and is commonly used in European countries. The grades A and B ...